Long-term immune checkpoint inhibitor therapy in a patient with metastatic nasopharyngeal carcinoma: a case report - Qing, Defeng; Lu, Zhiping; Lu, Heming (Frontiers in Immunology, 2025)
BackgroundImmunotherapy has revolutionized cancer treatment. However, the duration of treatment and the timing of discontinuation are major concerns. Current pivotal trials predominantly advocate for a fixed two-year regimen of immune checkpoint inhibitors (ICIs), exemplified by pembrolizumab and toripalimab, as first-line therapy for patients with advanced malignancies. Alternatively, for specific ICIs, including nivolumab, camrelizumab, and tislelizumab, continuous administration until disease progression has emerged as a favored approach. Nevertheless, whether to discontinue treatment after two years remains intensely debated within the medical community, underscoring the need for further research to clarify optimal treatment durations.Case presentationIn November 2018, a 44-year-old male presented with a persistent headache. Following a positive nasopharyngeal mucosal biopsy, he was diagnosed with non-keratinizing undifferentiated carcinoma of the nasopharynx cT4N2M0. An Epstein-Barr Virus (EBV) DNA load of 800 copies/mL was detected. The patient completed two cycles of induction chemotherapy with liposomal paclitaxel and nedaplatin, followed by platinum-based concurrent chemoradiotherapy, resulting in a progression-free survival (PFS) of 23.6 months. The EBV DNA load dropped significantly to 190 copies/mL. However, during a routine examination in January 2021, metastases in the lung and mediastinal lymph nodes were detected, and the EBV DNA load was measured at 2200 copies/mL. Consequently, surgical intervention was performed, followed by radiotherapy and two years of ICI treatment. Throughout the ICI maintenance period, the EBV DNA level remained consistently below the limit of detection. Remarkably, three months after treatment discontinuation, the patient exhibited a rebound in EBV DNA (1620 copies/mL). Nevertheless, imaging scans revealed no evidence of tumor progression. Following an ICI rechallenge, the patient’s EBV DNA load returned to undetectable levels. The patient continues the ICI therapy and has thus far achieved a PFS of 41.6 months.ConclusionEBV DNA levels could serve as an informative marker to predict the necessity of therapy discontinuation during immunotherapy maintenance. Notably, a post-discontinuation ICI rechallenge can still yield favorable outcomes potentially accredited to immune memory.